2017
DOI: 10.1016/j.eururo.2016.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Stage, Size, Grade, and Necrosis (SSIGN) Score for Clear Cell Renal Cell Carcinoma in Contemporary Patients

Abstract: Background The tumor stage, size, grade, and necrosis (SSIGN) score was originally defined using patients treated with radical nephrectomy (RN) between 1970 and 1998 for clear cell renal cell carcinoma (ccRCC), excluding patients treated with partial nephrectomy (PN). Objective To characterize the original SSIGN score cohort with longer follow-up and evaluate a contemporary series of patients treated with RN and PN. Design, setting, and participants Retrospective single-institution review of 3600 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 31 publications
2
81
1
1
Order By: Relevance
“…However, early and late relapse after surgery cannot be distinguished by TNM staging system which mainly depends on anatomical information instead of biological characteristics. The large variation in the relapse and prognosis of localized RCC patients with same clinicopathological features is attributed to the biological heterogeneity of cancer [10][11][12] . RCC patients with early relapse suffer from significantly poor OS rates comparing to those with late relapse [18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, early and late relapse after surgery cannot be distinguished by TNM staging system which mainly depends on anatomical information instead of biological characteristics. The large variation in the relapse and prognosis of localized RCC patients with same clinicopathological features is attributed to the biological heterogeneity of cancer [10][11][12] . RCC patients with early relapse suffer from significantly poor OS rates comparing to those with late relapse [18] .…”
Section: Discussionmentioning
confidence: 99%
“…As reason described above, prognosis even varies significantly in RCC patients with comparable clinicopathological characteristics and same tumor TNM stage. Despite researchers are exploring extensively the potential indicator or biomarker for predicting early relapse in RCC patients [10][11][12] , none of gene-based prognostic classifiers for predicting early relapse of RCC have been established. Although studies in clear cell RCC demonstrated that gene signature has better ability to both reflect heterogeneity of cancer and then accurately predict cancer prognosis [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients in this at-risk group can be considered candidates for adjuvant treatment. There is also a striking recent publication recommending the use of the SSIGN classification (28). In fact, it was stated that the calculated SSIGN score can be used to predict recurrence during 20-year follow-up after surgery.…”
Section: The Futurementioning
confidence: 99%
“…Often, ccRCC attacks the renal venous system, sometimes filling the renal vein and growing longer into the vena cava or even the right atrium. It is by far the most frequent type of kidney cancer in adults (2).…”
Section: Introductionmentioning
confidence: 99%